AN EXAMINATION VIDEO SUVEILLANCE SYSTEM USING A MICROCONTROLLER - BASED MOBILE DETECTION MODULE - Oyedeji Ayo Isaac,; Akinrogunde Oludare O,; Akovojeun Ezekiel Gbenupo, (International Engineering Journal For Research & Development, 2021)
Examination malpractice has left a deleterious effect in the educational system to the extent that the worth and competence of students cannot be measured through academic certificates only. This work is conducted with the objective to “develop and implement an “AN EXAMINATION VIDEO SUVEILLANCE SYSTEM USING A MICROCONTROLLER BASED MOBILE DETECTION MODULE” which can be used to detect the presence of signals in the range of 0.9GHz to 3GHz within a radius of one and a half metres and also produce a notification when the specified frequency range are detected. An activated mobile phone from a range of one and a half meters, captures the current view of the student (scene) as soon as the GPS data is received in order to prevent the use of the same in an examination halls and restricted places such as prisons, meeting places. The mobile phone detector detects any incoming/outgoing calls/SMS and then sends a wireless serial data using the Bluetooth module to the Invigilators android mobile application. The data sent, contains the GPS latitude and longitude coordinates of the detector device location where the mobile phone signal was detected. The android mobile application which was developed to receive the live feed video stream of the Wi-Fi Camera captures the current view of the student as soon as the GPS data is received. The received GPS data was then used to calculate the distance of the detector device from the invigilators mobile phone. The distance calculated was made possible using the Google Map API V2 which has the LatLng objects that determines the distances between two known latitudes and longitudes GPS coordinate data. The cell phone detector device also has a buzzer alarm which sounds an alarm to notify the invigilator when a cell phone is in use